Russia 1998 Revisited : Lessons for Financial Globalization - Pinto, Brian; Ulatov, Sergei (World Bank, Washington, DC, 2012)
In 1998, the Russian Federation experienced one of the most severe emerging market crises of the 1997-2001 periods. It occurred less than six months after the attainment of single-digit inflation, which was supposed to launch the economy onto a sustainable growth path. This note sets out why that occurred and discusses the lessons learned.